Emotional experiences of Korean correctional officers in response to incarcerated persons’ self-harm: a qualitative study - Lee, Ji-Hye; Park, Hyung-Ran (Frontiers in Psychology, 2025)
This study aimed to understand the experiences of correctional officers who deal closely with incarcerated persons who self-harm. Self-harm among incarcerated persons not only threatens the physical health of these individuals but also takes a toll on the mental health of correctional officers. A qualitative research method was utilised, with data collected through in-depth interviews of 15 participants from March 2022 to November 2022 and analysed utilising Colaizzi’s method. The results contained seven themes categorised into three theme clusters: ‘Suffering from psychological threat and pressure’, ‘Negative emotions encroaching into daily life’, and ‘Seeking stability by shifting perspective’. The findings underscore the need for trained professionals and programmes to effectively address the complex mental health challenges faced by correctional officers as they deal with incarcerated persons who self-harm.